2014
DOI: 10.5194/acp-14-8533-2014
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in assessing the environmental impact of amine emissions from a CO<sub>2</sub> capture plant

Abstract: Abstract. In this study, a new model framework that couples the atmospheric chemistry transport model system Weather Research and Forecasting–European Monitoring and Evaluation Programme (WRF-EMEP) and the multimedia fugacity level III model was used to assess the environmental impact of in-air amine emissions from post-combustion carbon dioxide capture. The modelling framework was applied to a typical carbon capture plant artificially placed at Mongstad, on the west coast of Norway. The study region is charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 55 publications
7
33
0
Order By: Relevance
“…Heikkilä et al (201 0) showed that regional climate simulations for the time period with the WRF model driven by the ERA-40 reanalysis better resolved the orographic lifting with 10-km horizontal resolution than with 30-km horizontal resolution. Karl et al (2014) analysed precipitation 1 elsevier_STOTEN_17722 data for 2007 at 14 meteorological stations in the region of Bergen, concluding that the WRF model, using identical configurations and meteorological boundaries as in the present study, underestimated the observed precipitation amount on a weekly basis at most stations by up to a factor of two. However, the weekly pattern of observed precipitation was well reproduced.…”
Section: Photolysis Scheme Fast-j Wild Et Al (2000)supporting
confidence: 46%
See 4 more Smart Citations
“…Heikkilä et al (201 0) showed that regional climate simulations for the time period with the WRF model driven by the ERA-40 reanalysis better resolved the orographic lifting with 10-km horizontal resolution than with 30-km horizontal resolution. Karl et al (2014) analysed precipitation 1 elsevier_STOTEN_17722 data for 2007 at 14 meteorological stations in the region of Bergen, concluding that the WRF model, using identical configurations and meteorological boundaries as in the present study, underestimated the observed precipitation amount on a weekly basis at most stations by up to a factor of two. However, the weekly pattern of observed precipitation was well reproduced.…”
Section: Photolysis Scheme Fast-j Wild Et Al (2000)supporting
confidence: 46%
“…The reactivity of MEA in the study region was overall higher in the WRF--Chem simulations than predicted by the WRF--EMEP model framework presented in Karl et al (2014). However, due to lower NO x levels in WRF--Chem, the average production yield of MEA-nitramine in the reaction between MEA and OH was only 0.1%, a factor of 9 lower than in WRF--EMEP.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations